Vocabulary frequency and dispersion in Japanese junior high school EFL textbooks - Ryan Klinger (Vocabulary Learning and Instruction)
Studies relating to the vocabulary items within EFL textbooks have revealed a divergence from well-researched wordlists such as the New General Service List (NGSL) (Browne et al., 2013), and the BNC/COCA wordlist (Nakayama, 2022; Sun and Dang, 2020). In Japan, the Ministry of Education, Culture, Sports, Science and Technology (MEXT) recently updated its course of study in 2019 to increase the target vocabulary for junior high school students from 1,200 words to a range between 1,600 and 1,800 words, in addition to the 600 to 700 words taught in elementary school. To analyze the content of the increased vocabulary for Japanese junior high school students, this study examined a corpus of six EFL textbooks from the New Horizon series: three elementary texts and three junior high school texts, (published between 2020 and 2021) using the new JACET8000 wordlist (2016), generating data pertaining to lexical coverage, in-corpus frequency, and in-corpus dispersion. It was found that 42.9% of the first 3,000 words from the JACET list were not found in the corpus, and 50.4% of the high-frequency words studied by junior high school students occurred less than two times within the corpus. Additionally, 35% of analyzed words were found to have a dispersion value of zero, indicating that several items were isolated into single units of study. Lastly, factors contributing to lexical difficulty of the textbooks were also examined.